Transcriptomic analyses of ovarian clear-cell carcinoma with concurrent endometriosis - Collins, Kaitlyn E.; Wang, Xiyin; Klymenko, Yuliya; Davis, Noah B.; Martinez, Maria C.; Zhang, Chi; So, Kaman; Buechlein, Aaron; Rusch, Douglas B.; Creighton, Chad J.; Hawkins, Shannon M. (Frontiers in Endocrinology, 2023)
Endometriosis, a benign inflammatory disease whereby endometrial-like tissue grows outside the uterus, is a risk factor for endometriosis-associated ovarian cancers. In particular, ovarian endometriomas, cystic lesions of deeply invasive endometriosis, are considered the precursor lesion for ovarian clear-cell carcinoma (OCCC). To explore this transcriptomic landscape, OCCC from women with pathology-proven concurrent endometriosis (n=4) were compared to benign endometriomas (n=4) by bulk RNA and small-RNA sequencing. Analysis of protein-coding genes identified 2449 upregulated and 3131 downregulated protein-coding genes (DESeq2, P<0.05, log2 fold-change>|1|) in OCCC with concurrent endometriosis compared to endometriomas. Gene set enrichment analysis showed upregulation of pathways involved in cell cycle regulation and DNA replication and downregulation of pathways involved in cytokine receptor signaling and matrisome. Comparison of pathway activation scores between the clinical samples and publicly-available datasets for OCCC cell lines revealed significant molecular similarities between OCCC with concurrent endometriosis and OVTOKO, OVISE, RMG1, OVMANA, TOV21G, IGROV1, and JHOC5 cell lines. Analysis of miRNAs revealed 64 upregulated and 61 downregulated mature miRNA molecules (DESeq2, P<0.05, log2 fold-change>|1|). MiR-10a-5p represented over 21% of the miRNA molecules in OCCC with endometriosis and was significantly upregulated (NGS: log2fold change=4.37, P=2.43e-18; QPCR: 8.1-fold change, P<0.05). Correlation between miR-10a expression level in OCCC cell lines and IC50 (50% inhibitory concentration) of carboplatin in vitro revealed a positive correlation (R2=0.93). MiR-10a overexpression in vitro resulted in a significant decrease in proliferation (n=6; P<0.05) compared to transfection with a non-targeting control miRNA. Similarly, the cell-cycle analysis revealed a significant shift in cells from S and G2 to G1 (n=6; P<0.0001). Bioinformatic analysis predicted that miR-10a-5p target genes that were downregulated in OCCC with endometriosis were involved in receptor signaling pathways, proliferation, and cell cycle progression. MiR-10a overexpression in vitro was correlated with decreased expression of predicted miR-10a target genes critical for proliferation, cell-cycle regulation, and cell survival, including [SERPINE1 (3-fold downregulated; P<0.05), CDK6 (2.4-fold downregulated; P<0.05), and RAP2A (2-3-fold downregulated; P<0.05)]. These studies in OCCC suggest that miR-10a-5p is an impactful, potentially oncogenic molecule, which warrants further studies.